MENGGAGAS NERACA SYARI’AH BERBASIS MAAL: KONTEKSTUALISASI ’’KEKAYAAN ALTRUISTIK ISLAMI” - Mulawarman, Aji Dedi (UI Scholars Hub, 2007)
The objective o f this research is to formulate Shari 'ate Balance Sheet from the real transaction and business habitus o f Indonesian Moslem Society. Formulation is conducted by utilising Extension o f Integrated Islamic Hyperstructuralism Methodology. In that methodology, conventional concept o f wealth and Baydoun and Willett’s (1994) balance sheet are refined by Shari’ate Accounting. The result is then refined by (Islamic) Technosystem and Extension o f Pierre Bourdieu’s Constructivist Structuralism to generate Shari 'ate Balance Sheet. The major result shows that maal is form o f Islamic and Altruistic Wealth. This means that wealth must: (1) have an holistic values (material, mental and spiritual); (2) owned by a wider-stakeholders (Allah, direct, indirect, and nature); and (3) based on shari ’ate ways (halal, thoyib and free from riba). The consequence o f the major result are all the elements in the Shari’ate Balance Sheet based on: (1) obedience (abd’ Allah) assets, liabilities and equities, and (2) creativity (khalifatullah fil ardh) assets, liabilities and equities.